2018
DOI: 10.1002/hpm.2502
|View full text |Cite
|
Sign up to set email alerts
|

Do private hospitals outperform public hospitals regarding efficiency, accessibility, and quality of care in the European Union? A literature review

Abstract: SummaryEuropean countries have enhanced the scope of private provision within their health care systems. Privatizing services have been suggested as a means to improve access, quality, and efficiency in health care. This raises questions about the relative performance of private hospitals compared with public hospitals. Most systematic reviews that scrutinize the performance of the private hospitals originate from the United States. A systematic overview for Europe is nonexisting. We fill this gap with a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
77
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 68 publications
11
77
0
3
Order By: Relevance
“…20 At the same time, findings from both the UK and the US suggest that ITCs might be cherry-picking and treat less-complex patients compared with hospitals. [20][21][22][23][24][25] From the demand side, it seems that the characteristics of patients seeking care from ITCs differ from those of patients seeking care from hospitals. The independent sector in the UK historically serves the interests of private practices of NHS consultants and target a more affluent clientele with additional amenities and shorter waiting lists.…”
Section: Kruse Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…20 At the same time, findings from both the UK and the US suggest that ITCs might be cherry-picking and treat less-complex patients compared with hospitals. [20][21][22][23][24][25] From the demand side, it seems that the characteristics of patients seeking care from ITCs differ from those of patients seeking care from hospitals. The independent sector in the UK historically serves the interests of private practices of NHS consultants and target a more affluent clientele with additional amenities and shorter waiting lists.…”
Section: Kruse Et Almentioning
confidence: 99%
“…In contrast, the independent sector in the UK charged higher prices than NHS hospitals (unclear whether this disparity still exists), and evidence points to the fact that ITCs in the UK are not always more efficient—only patients with hip or knee replacements had a shorter length of stay when treated in an ITC . At the same time, findings from both the UK and the US suggest that ITCs might be cherry‐picking and treat less‐complex patients compared with hospitals …”
Section: Introductionmentioning
confidence: 99%
“…To the contrary, a study in Germany examining changes in efficiency after privatization demonstrated that conversion from public to private for-profit status resulted in an increase in efficiency between 2.9% and 4.9%, which also appeared to be permanent rather than a transient change [9]. Still others have concluded that there is no clear evidence that private hospital ownership -non-profit and for profits -is associated with higher efficiency compared to public hospital ownership [26,27].…”
Section: Ownershipmentioning
confidence: 97%
“…En otra revisión de este año, etiquetada por los propios autores como «realista», se compara el desempeño de los hospitales públicos con los hospitales privados en cuanto a eficiencia, accesibilidad y calidad de atención en la Unión Europea, sintetizando estudios de Italia, Alemania, Reino Unido, Francia, Grecia, Austria, España y Portugal (Kruse et al, 2018). La mayoría de la evidencia sugiere que los hospitales públicos son al menos tan eficientes o más que los hospitales privados.…”
Section: Sobre La Relativa Eficiencia De La Prestación Pública Y Privadaunclassified